2008
DOI: 10.1001/archneur.65.7.887
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Urban Differences in Acute Stroke Management Practices

Abstract: cute stroke management practices in rural areas of the United States are suboptimal, which creates an unacceptable health disparity between urban patients with stroke and their rural counterparts. The existing gap between urban and rural stroke care may widen in the future as more urban-tested interventions are incorporated into the treatment of acute stroke. We conducted a PubMed search to identify all the articles published from 1997 to 2007 that addressed acute stroke, paramedics, ambulances, emergency serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 39 publications
0
98
1
1
Order By: Relevance
“…3 The shortage of stroke specialists and other physicians with experience administering this drug in rural areas is a substantial barrier preventing more widespread tPA use. 33 Telestroke has the potential to lower this barrier by providing longdistance consultation to such areas, in effect increasing the expertise, and therefore quality, of stroke care at rural hospitals.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…3 The shortage of stroke specialists and other physicians with experience administering this drug in rural areas is a substantial barrier preventing more widespread tPA use. 33 Telestroke has the potential to lower this barrier by providing longdistance consultation to such areas, in effect increasing the expertise, and therefore quality, of stroke care at rural hospitals.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Urban Japanese diets typically have lower sodium, higher calcium, and higher animal protein than rural Japanese diets, 28 and cities tend to have better access to emergency health services that can help prevent fatal outcomes from stroke. 29 Similar factors may help explain the lower mortality due to heart disease in urban Japan. However, a recent study revealed that the decline in mortality due to coronary heart disease and stroke since the 1970s was notably smaller in men aged 30-49 in Tokyo and Osaka, and has plateaued.…”
Section: Discussionmentioning
confidence: 98%
“…These are likely to be influenced by small-area disparities in the risk factors for these diseases as well as in the availability, accessibility, and utilization of emergency healthcare services. 29 Interventions to improve health equity, thus, require attention to aspects of gender, disease types, and the broader determinants of health. 32 In order to develop policy and program interventions that can effectively address the issues uncovered by the kind of data presented in this study, there needs to be more evidence on the causes of these outcomes which can contribute to theoretical development about causes of health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…15 The geographic disparity in access to stroke care for a large proportion of the US population can only increase the existing disparity of stroke care between rural and urban areas. 16 Unfortunately, it is clear that the number of PSCs needed to improve the coverage to acceptable levels is quite large.…”
Section: Discussionmentioning
confidence: 99%